Defining Microbiome Readiness for Surgery: Dietary Prehabilitation and Stool Biomarkers as Predictive Tools to Improve Outcome. Issue 5 (4th November 2022) - Keskey, Robert; Papazian, Emily; Lam, Adam; Toni, Tiffany; Hyoju, Sanjiv; Thewissen, Renee; Zaborin, Alexander; Zaborina, Olga; Alverdy, John C.
Abstract : Objectives: Determine whether preoperative dietary prehabilitation with a low-fat, high-fiber diet reverses the impact of Western diet (WD) on the intestinal microbiota and improves postoperative survival Background: We have previously demonstrated that WD fed mice subjected to an otherwise recoverable surgical injury (30% hepatectomy), antibiotics, and a short period of starvation demonstrate reduced survival (29%) compared to mice fed a low-fat, high-fiber standard chow (SD) (100%). Methods: Mice were subjected to 6 weeks of a WD and underwent dietary pre-habilitation (3 days vs 7 days) with a SD prior to exposure to antibiotics, starvation, and surgery. 16S rRNA gene sequencing was utilized to determine microbiota composition. Mass spectrometry measured short chain fatty acids and functional prediction from 16S gene amplicons were utilized to determine microbiota function. Results: As early as 24 hours, dietary prehabilitation of WD mice resulted in restoration of bacterial composition of the stool microbiota, transitioning from Firmicutes dominant to Bacteroidetes dominant. However, during this early pre-habilitation (ie, 3 days), stool butyrate per microbial biomass remained low and postoperative mortality remained unchanged from WD. Microbiota function demonstrated reduced butyrate contributing taxa as potentially responsible for failed recovery. In contrast, after 7 days of prehabilitation (7DP), there was greater restoration of butyrate producing taxa and survival after surgery improved (29% vs 79% vs 100%: WD vs 7DP vs SD, P < 0.001). Conclusions: The deleterious effects of WD on the gut microbiota can be restored after 7 days of dietary prehabilitation. Moreover, stool markers may define the readiness of the microbiome to withstand the process of surgery including exposure to antibiotics and short periods of starvation.